Electrical properties of single CdTe nanowires - Matei, Elena; Florica, Camelia; Costas, Andreea; Toimil-Molares, María Eugenia; Enculescu, Ionut (Beilstein Journal of Nanotechnology, 2015)
Ion track, nanoporous membranes were employed as templates for the preparation of CdTe nanowires. For this purpose, electrochemical deposition from a bath containing Cd and Te ions was employed. This process leads to high aspect ratio CdTe nanowires, which were harvested and placed on a substrate with lithographically patterned, interdigitated electrodes. Focused ion beam-induced metallization was used to produce individual nanowires with electrical contacts and electrical measurements were performed on these individual nanowires. The influence of a bottom gate was investigated and it was found that surface passivation leads to improved transport properties.
Keywords: CdTe; electrodeposition; nanowires; transport properties